2015
DOI: 10.3402/gha.v8.24271
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening health facilities for maternal and newborn care: experiences from rural eastern Uganda

Abstract: BackgroundIn Uganda maternal and neonatal mortality remains high due to a number of factors, including poor quality of care at health facilities.ObjectiveThis paper describes the experience of building capacity for maternal and newborn care at a district hospital and lower-level health facilities in eastern Uganda within the existing system parameters and a robust community outreach programme.DesignThis health system strengthening study, part of the Uganda Newborn Study (UNEST), aimed to increase frontline hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 12 publications
2
74
0
Order By: Relevance
“…The MANIFEST approach demonstrated that it is possible to have positive and collegial relationships between health workers and supervisors. The changes in the use of support supervision in improving the quality of maternal and newborn care services has also been reported by other studies conducted in low-income countries [10,12–14]. …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The MANIFEST approach demonstrated that it is possible to have positive and collegial relationships between health workers and supervisors. The changes in the use of support supervision in improving the quality of maternal and newborn care services has also been reported by other studies conducted in low-income countries [10,12–14]. …”
Section: Discussionsupporting
confidence: 68%
“…Available evidence highlights the importance of support supervision in strengthening relationships within the system, identification and resolution of problems, optimizing the allocation of resources, motivating health workers, promoting the use of standard procedures, and teamwork [10,11]. Support supervision also provides opportunities for regular feedback and therefore promotes skill building through appropriate strategies, such as training and mentorships [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant ethnic group in the HDSS is the Basoga, a bantu-speaking group which make up 8% of Uganda’s population. The HDSS is served by one 100-bed hospital and at least 19 government-run and private-sector health centres [17]. A rising proportion of women in the Central East region, over two-thirds, deliver at health facilities [18].…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged direct SSC between infants and caregivers is the cornerstone of KMC . Most studies of KMC have taken place in dedicated KMC wards , where staff were trained to care for both newborn infants and post‐partum women. Intermittent SSC may occur in the absence of a KMC ward or where adequate space to practice continuous SSC does not exist or is not used.…”
Section: Introductionmentioning
confidence: 99%